Comparison of Percutaneous Radiofrequency Ablation for Subcapsular and Non-Subcapsular Colorectal Cancer Liver Metastases - Fan, Hongjie; Wang, Xiaoyan; Qu, Jiali; Lu, Wei; Xu, Shufeng; Wu, Xia; Xia, Jingya; Zhang, Yanhua; Sun, Jihong; Yang, Xiaoming (Frontiers in Oncology, 2021)
Purpose To evaluate the efficacy and safety of percutaneous radiofrequency ablation (RFA) for subcapsular colorectal cancer liver metastases (CLMs). Materials and Methods With the approval of the Institutional Review Board, the clinical data of CLM patients who underwent percutaneous RFA for the first time from August 2010 to August 2020 were continuously collected. All CLMs were divided into subcapsular and non-capsular groups. Baseline characteristic data, technical effectiveness, minimal ablative margin, complications, local tumor progression (LTP), and overall survival (OS) between the two groups were analyzed using the t-test or chi-square test. A Cox regression model was used to evaluate the prognostic factors of LTP. Results One hundred and ninety-nine patients (124 males; mean age, 60.2 years) with 402 CLMs (221 subcapsular; mean size, 16.0 mm) were enrolled in the study. Technical effectiveness was achieved in 93.5% (376/402) of CLMs, with a major complication rate of 5.5%. Compared with non-subcapsular tumors, the minimal ablative margin achieved in subcapsular CLM was smaller (χ2 = -8.047, P < 0.001). With a median follow-up time of 23 months (range, 3−96 months), 37.1% of the tumors had LTP. The estimated cumulative OS at 1, 3, and 5 years was 96.1%, 66.0%, and 44.2%, respectively. There were no statistically significant differences between the two groups in terms of technical effectiveness (χ2 = 0.484, P = 0.487), major complications (χ2 = 0.082, P = 0.775), local tumor progression-free survival (LTPFS) (χ2 = 0.881, P = 0.348), and OS (χ2 = 2.874, P = 0.090). Minimal ablative margin, tumor size (≥20 mm), and technical effectiveness were predictors of LTP (all P < 0.05). Conclusion RFA is a safe and effective technique for local tumor control of subcapsular CLMs.